Chloride Transport of High Alumina Cement Mortar Exposed to a Saline Solution - Hee Jun Yang; Sung Ho Jin; Ki Yong Ann (Advances in Materials Science and Engineering)
Chloride transport in different types of high alumina cement (HAC) mortar was investigated in this study. Three HAC cement types were used, ranging from 52.0 to 81.1% of aluminum oxides in clinker. For the development of the strength, the setting time of fresh mortar was measured immediately after mixing and the mortar compressive strength was cured in a wet chamber at 25 ± 2°C and then measured at 1–91 days. Simultaneously, to assess the rate of chloride transport in terms of diffusivity, the chloride profile was performed by an exposure test in this study, which was supported by further experimentation including an examination of the pore structure, chloride binding, and chemical composition (X-ray diffraction) analysis. As a result, it was found that an increase in the Al2O3 content in the HAC clinker resulted in an increase in the diffusion coefficient and concentration of surface chloride due to increased binding of chloride. However, types of HAC did not affect the pore distribution in the cement matrix, except for macro pores.